Attention as a determinant of task performance: From basics to applications - Tetsuo Kida; Emi Tanaka; Ryusuke Kakigi (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Attention is the ability to extract task-relevant information and reject irrelevant information in order to avoid excessive information processing in the nervous system, and influences task performance in daily life including physical and sporting activities. Basic attentional phenomena at the behavioral and neural levels have recently been employed as measures of attentional functions to examine the effects of exercise training and motor learning in the real world. However, these basic phenomena have been demonstrated in strictly manipulated laboratory experiments; therefore, it currently remains unclear whether they may be applied to the examination of attentional functions in real-world conditions. We herein briefly review basic attentional theories derived from a number of dual-task experiments and discuss their applicability to a more realistic world.